THE UNEXPECTED NEGATIVE IMPACT OF SERVICE QUALITY ON RETAIL PERFORMANCE IN TRADITIONAL BUILDING STORES: EVIDENCE FROM ASBESTOS-CONTAINING PRODUCTS IN SURABAYA RAYA - Dendy Tirtoadisuryo (Journal of Development Economics and Digitalization, Tourism Economics, 2025)
This study aims to analyze the unexpected negative impact of service quality on retail performance in the sale of asbestos-based products in traditional building stores in Greater Surabaya. The research method used was quantitative with a cross-sectional design and Partial Least Squares Structural Equation Modeling (PLS-SEM) analysis, involving 120 building stores that met purposive sampling criteria. The results showed that service quality had a significant negative effect on marketing performance (β = –0.259; p < 0.01) and indirectly reduced sales performance through the mediation of marketing performance (β = –0.087; p < 0.01). The findings also indicated that asbestos knowledge reinforced the negative effect of service quality on marketing performance (β = –0.214; p < 0.01), indicating that consultative services actually increase perceived health risks, decrease trust, and weaken purchase intentions. In conclusion, service quality in the context of high-risk products like asbestos can be a strategic liability, not an asset, and therefore, service strategies need to be directed at educating consumers about safer product alternatives.